Sports business and multisided markets: Towards a new analytical framework? - Oliver Budzinski; Janina Satzer (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2011)
Despite still being younger than a decade, the theory of multisided markets has offered numerous valuable insights for the analysis of industries in which a supplier serves two distinct customer groups that are indirectly interrelated through externalities. Examples include payment systems, matching agencies, commercial media, and software platforms. However, professional sports markets have largely been neglected so far in this kind of research although they possess the characteristics of multisided markets. This conceptual paper contributes to filling this gap by describing the platform elements of professional suppliers of sports events and conceptually outlining issues where an application of this theoretical framework is likely to provide valuable insights and to add to the existing knowledge. Among these problems are integrative pricing strategies of sports clubs towards such different customer groups like attendees, broadcasters, sponsors, etc., including their welfare and antitrust implications, design decisions of sports associations in order to promote positive feedback loops among the customer groups as well as management strategies to reinforce positive externalities among customer groups and alleviate negative ones.
Keywords: 330; sports economics; sports management; two-sided markets; multisided platforms; professional sports business; pricing strategies broadcasting rights; Sportökonomik; Professioneller Sport; Sportmanagement; Sport; Management; Marktstruktur; Übertragungsrechte; Betriebliche Preispolitik